Case Report of Diabetes Zoo-housed Black Macaque (Macaca nigra ) Treated with Long-acting Insulin - SAKAI, Hidefumi; TSUKADA, Koji; GOSHIMA, Wataru; SADO, Akihiro; OSAWA, Natsuo; KUROKAWA, Akemi; SHIBATA, Chikako; HAYASHI, Kotaro; Takiguchi, Mitsuyoshi; UEDA, Kaoru; MAENO, Yoshichika; KAKISAKA, Keita; et al. (Japanese Journal of Zoo and Wildlife Medicine, 2024)
The black macaque (Macaca nigra ) is a threatened macaque monkey species found in Indonesia. We present a caseof a 14-year-old male black macaque that presented with symptoms of increased water intake, vision impairment,and emaciation. Examinations found high blood/urine glucose levels, and the patient was diagnosed with diabetesmellitus (DM). Long-acting insulin and glargine administration improved blood chemistry parameters and nutritionalstatus. There was moderate correlation coefficient between glycoalbumin (GA) and average blood glucose levels. Theadministration of glargine and evaluation of GA levels can be used for the management of DM in macaque monkeys.